Manifestation of the Upper Hubbard band in the 2D Hubbard model at low electron density: Низкоразмерные структуры - Kagan, M.Yu.; Val’kov, V.V.; Woelfle, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We consider the 2D Hubbard model in the strong-coupling case (U >> W) and at low electron density (nd 2 << 1).We find an antibound state as a pole in the two-particle T-matrix. The contribution of this pole in the self-energy reproduces a two-pole structure in the dressed one-particle Green-function similar to the Hubbard-Iapproximation. We also discuss briefly the Engelbrecht-Randeria mode which corresponds to the pairing of two holes below the bottom of the band for U >> W and low electron density. Both poles produce nontrivialcorrections to Landau Fermi-liquid picture already at low electron density but do not destroy it in 2D.